Scene Understanding by Labeling Pixels. - GOULD, STEPHEN; XUMING HE (Communications of the ACM, 2014)
The article discusses the pixel-labeling or semantic-segmentation in programming computers to allow automatic interpretation of the image content. Topics discussed include the challenge in artificial intelligence and computer vision, hierarchical segmentation or scene parsing to produce refined view of the scene, the process in pixel labeling, probabilistic model known as conditional Markov random field (CRF) use in most methods for pixel labeling and partition function that ensures the probability distribution.